The Effect Of Fishing Ball Therapy And Puzzle Therapy On Cognitive Function In Elderly Patients With Dementia At Club Bugar Ideal, Bojonggede District, Bogor Regency In 2025 - Abdullah Assjidiq; Agus Purnama; Ristinawati Ristinawati; Siti Rafika Putri (International Journal of Health Engineering and Technology, 2026)
Dementia increases with age, especially in the elderly population. Dementia is a clinical syndrome with progressive decline in cognitive function that interferes with independence and daily activities. Dementia can also cause serious complications, such as a decline in quality of life and health problems that are often the leading causes of mortality. To determine the effect of fishing ball therapy and puzzle therapy on cognitive function in elderly people with dementia at Club Bugar Ideal, Bojonggede District. This study was a quantitative study using a quasi-experimental approach with one equivalent control group pretest-posttest design. Data collection was conducted using the Mini Mental State Examination (MMSE) questionnaire. Data analysis was performed using univariate and bivariate analysis with the Shapiro-Wilk test using Jamovi 2.6.26 software. The average age of respondents was over 60 years old. In terms of gender, the majority were female, with 27 respondents (69.2%). In terms of education, the majority had only completed elementary school, with 17 respondents (43.6%). In terms of employment, the majority were unemployed, with 29 respondents (74.4%). In terms of medical history, the majority had a history of illness, with 23 respondents (59%). Based on the results of the group A fishing ball p value (0.181) > 0.05 and group B Puzzle p value (0.095) > 0.05, meaning that there was no effect of therapy in either the fishing ball or puzzle groups on the cognitive function of the elderly before and after therapy, whereas there was an effect of therapy in group C (fishing ball and puzzle) on the cognitive function of the elderly before and after therapy. The results of the difference test showed no significant differences between the therapy groups, namely fishing ball therapy (A), puzzle therapy (B), and a combination of fishing ball and puzzle therapy (C). The p-values for the comparisons between groups were (A–B p=0.594; A–C p=0.440; B–C p=0.804). Non-pharmacological therapy, namely a combination of fishing ball and puzzle therapy, can improve cognitive function in elderly people with dementia.